Antioxidant activity of pereskia herb by infrared spectroscopy - Khan, Md Sharif; Rahman, Md. M.; Sarker, Md. Zaidul Islam; Marriott, Philip J. (2014)
Pereskia bleo is a species of primitive cactus Pereskia that is distinguished by its green leaves. In the present study, Fourier transformed infrared spectroscopy (FTIR) of P. bleo leaf extracts were subjected to multivariate analysis allowing for rapid prediction of antioxidant activity as well as identification of contributing functional groups. A total of twenty four different extracts were prepared using different extracting solvents. Antioxidant activities were measured by DPPH (1,1- diphenyl-2-picrylhydrazyl) radical scavenging assay; the same extracts were -1-1 fingerprinted by FTIR over the range of 4000–400 cm at resolution of 2 cm. Multivariate orthogonal partial least square (OPLS) model was employed to correlate the FTIR spectrum with antioxidant activity of different extracts. A three components OPLS with R2Y of 0.88 and Q2 of 0.86 was constructed and its quality was proven by two different validation tests namely, internal cross-validation and true external test. For external validation, bioactivity of three new extracts of P. bleo was predicted using the OPLS model, and checked for bioactivity to confirm the model prediction. From the line loading plot of OPLS, -OH, -NH and -CH were identified as responsible functional groups for the activity of the sample. A successful OPLS model was developed using FTIR spectroscopy as a rapid method to predict bioactivity of samples.